Domestic and cross border spillover effects of corporate tax policy in Africa - (:unkn) unknown (My University, 2019)
This paper examines spillover effects in corporate tax policy for African economies. Using a balanced panel data in statutory corporate income tax (CIT) rate for 34 African countries over the period 1995-2013, we find positive interaction between CIT rates in Africa only when common time trend effects are not controlled. We conclude that the evidence of pure corporate tax competition among African countries is weak. These countries' tendency to implement similar fiscal policies under the common intellectual assistance may explain the positive slope reaction between their CIT rates. Regarding corporate tax base spillovers, estimation results indicate that cuts in foreign countries’ average corporate tax rate reduce the host country’s corporate tax base. When the host country reacts to a one percentage point cut in foreign countries’ CIT rates by cutting its own CIT rate in the same proportion, this ultimately results in a net erosion of its corporate tax base by 0.4%. This represents a 2.3 % loss of corporate tax revenue. Moreover, we find strategic complement responses in corporate tax base policies suggesting that countries react to the uptake of measures that tend to reduce the corporate tax burden in other countries by also undertaking similar measures.
Keywords: African Research